Are common names becoming less common? The rise in uniqueness and individualism in Japan - Ogihara, Yuji; Fujita, Hiroyo; Tominaga, Hitoshi; Ishigaki, Sho; Kashimoto, Takuya; Takahashi, Ayano; Toyohara, Kyoko; Uchida, Yukiko (Frontiers in Psychology, 2015)
We examined whether Japanese culture has become more individualistic by investigating how the practice of naming babies has changed over time. Cultural psychology has revealed substantial cultural variation in human psychology and behavior, emphasizing the mutual construction of socio-cultural environment and mind. However, much of the past research did not account for the fact that culture is changing. Indeed, archival data on behavior (e.g., divorce rates) suggest a rise in individualism in the U.S. and Japan. In addition to archival data, cultural products (which express an individual’s psyche and behavior outside the head; e.g., advertising) can also reveal cultural change. However, little research has investigated the changes in individualism in East Asia using cultural products. To reveal the dynamic aspects of culture, it is important to present temporal data across cultures. In this study, we examined baby names as a cultural product. If Japanese culture has become more individualistic, parents would be expected to give their children unique names. Using two databases, we calculated the rate of popular baby names between 2004 and 2013. Both databases released the rankings of popular names and their rates within the sample. As Japanese names are generally comprised of both written Chinese characters and their pronunciations, we analyzed these two separately. We found that the rate of popular Chinese characters increased, whereas the rate of popular pronunciations decreased. However, only the rate of popular pronunciations was associated with a previously validated collectivism index. Moreover, we examined the pronunciation variation of common combinations of Chinese characters and the written form variation of common pronunciations. We found that the variation of written forms decreased, whereas the variation of pronunciations increased over time. Taken together, these results showed that parents are giving their children unique names by pairing common Chinese characters with uncommon pronunciations, which indicates an increase in individualism in Japan.